2017
DOI: 10.1039/c6ra28743c
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient metal organic framework (MOF)-based copper catalysts for the base-free aerobic oxidation of various alcohols

Abstract: Copper containing metal organic frameworks (MOFs) are found to be highly efficient heterogeneous catalysts for alcohol oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…The Cu 2p spectrum shows two peaks at 953.5 and 933.8 eV, corresponding to Cu 2p 1/2 and Cu 2p 3/2 of Cu(II), respectively (Figure S7a, Supporting Information). [ 24,25 ] The N 1s spectrum shows the presence of a split with maxima at 401.4 and 399.4 eV (Figure S7b, Supporting Information), suggesting strong coordination with Cu(II) and partial charge transfer from nitrogen lone pair to copper. [ 26,27 ] In the Cl 2p spectrum, the two peaks at 199.3 and 197.7 eV corresponds to Cl 2p 1/2 and Cl 2p 3/2 , respectively (Figure S7c, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…The Cu 2p spectrum shows two peaks at 953.5 and 933.8 eV, corresponding to Cu 2p 1/2 and Cu 2p 3/2 of Cu(II), respectively (Figure S7a, Supporting Information). [ 24,25 ] The N 1s spectrum shows the presence of a split with maxima at 401.4 and 399.4 eV (Figure S7b, Supporting Information), suggesting strong coordination with Cu(II) and partial charge transfer from nitrogen lone pair to copper. [ 26,27 ] In the Cl 2p spectrum, the two peaks at 199.3 and 197.7 eV corresponds to Cl 2p 1/2 and Cl 2p 3/2 , respectively (Figure S7c, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…82 This amine functionalized MOF was treated with CuCl2 to obtain Cu(II)/MOF-NH2 composite ( Figure 10) and its activity in the oxidation of BA in the presence of TEMPO evaluated. 55 Under the optimized reaction conditions, Cu(II)/MOF-NH2 and TEMPO as co-catalyst afforded in acetonitrile under air atmosphere at 70 o C complete BA conversion. In contrast, MOF-N3 and MOF-NH2 gave no conversion of BA, which confirmed that the oxidation of BA to benzaldehyde is catalysed by Cu.…”
Section: With Permission From Wileymentioning
confidence: 95%
“…X-ray photoelectron spectroscopy (XPS) possesses untapped potential to ascertain whether emission-quenching molecules are adsorbed to the MOF surfaces or possibly internalized within the pores. XPS can determine metal oxidation states in MOFs 18,19 and MOF composites, 20 as well as quantify catalyst decomposition due to side-reactions. 21 XPS is sensitive to near-surface chemical environments, 22 and angle-resolved XPS (ARXPS) further utilizes the attenuation of sub-surface electrons to quantify surface vs. bulk contributions to a photoelectron spectrum.…”
Section: Introductionmentioning
confidence: 99%